MRAS Based Sensorless and Sensor Vector Control and Smooth Transient Between Them - Jakub Vonkomer; Milan Zalman (Communications - Scientific letters of the University of Zilina, 2011)
Dynamic control, like vector control is an essential feature of every modern AC drive. In some cases it might be very important to provide continuous operation in case of encoder failure. It further means that the transient between sensor vector control and sensorless vector control has to be smooth. To obtain that a modified vector and sensorless vector control algorithms were designed. To allow smooth transitions, both sensor and sensorless control share common flux model. In this paper a novel robust MRAS-based speed estimator based on error between current estimators output and measured current and modifications of direct sensor vector control are presented. Theoretical analysis of estimators and design of adaptation loop is described. Finally, simulation and experimental results are shown.